CHANGES IN HEMATOLOGICAL PROFILES OF ALBINO RATS UNDER CHLORPYRIFOS TOXICITY - Y. SAVITHRI; P. RAVI SEKHAR; P. JACOB DOSS (International Journal of Pharma and Bio Sciences, 2010)
Hematology is defined as the branch of biology, which deals with the morphology of blood and blood forming organs. Haematological profiles of blood can provide important information about the internal environment of the organism. In the present investigation the effect of chlorpyrifos, an organophosphate compound on the blood components is determined in albino rats. The present investigation was aimed to examine the haematological changes of of albino rats with oral sub lethal (20 mg/kg) administration of chlorpyrifos as single, double and multiple doses with 48 hr intervals. The decrease in RBC count, Hb and PCV observed in the present investigation could be described are retarded haemopoisis, destruction and shrinkage of RBC. MCV, MCH and MCHC showed significant decrease in all doses in the present investigation, due to destruction of RBC (size and shape) and decrease in Hb synthesis and hemoglobin content. These symptoms imply the microcytic- hypo chromic anemia. A decreased percentage of neutrophils in peripheral blood observed in animals poisoned with chlorpyrifos may suggest, neutrophils involves in phagocytosis during xenobiotic intoxication, during which some of the neutrophils might have ruptured.